Clinicopathological profile and its association with endoscopic findings in dyspeptic patients in a tertiary care hospital: A cross-sectional study - Shetty, Aarthik; Yeshavanth G; Siddesh G; Nikhil Kumar DG (Asian Journal of Medical Sciences, 2024)
Background: The prevalence of dyspepsia in general practice consultations ranges from 4% to 5%, whereas it accounts for approximately 20–40% of consultations in the field of gastroenterology. Aims and Objectives: This study was carried out with the objective of estimating the percentage of Helicobacter pylori-infected people who havedyspepsia and exploring the relationship between infection and clinical manifestation. Materials and Methods: This was a hospital-based observational study conducted at a tertiary care teaching health-care facility from January 2023 to June 2023. All 50 patients with symptoms of dyspepsia were included in the study with the help of non-probability purposive sampling after their written and informed consent. A pre-designed and pre-tested structured pro forma was used to collect detailed history, clinical findings, and endoscopic findings from patients with dyspepsia. Gastritis and ulceration characteristics were observed by endoscopy, while histopathological examination (HPE) and rapid urease test (RUT) (for confirmation of H. pylori) were performed on endoscopy-obtained biopsy specimens. Results: Mean age of the patients was 46.69±15.78 with 65.4% (n=34) being males. The sample was classified into cases positive for H. pylori (13; 25%) and cases negative for H. pylori (39; 75%), according to the RUT outcome, 21.20% (n=11) had a history of smoking, 25% (n=13) had Type II DM, and 25% of patients presented with upper abdominal bloating and epigastric pain. On endoscopy, the majority of patients revealed grade III (n=22, 42.30%) gastritis and no ulceration (n=29, 55.80%), with the maximum showing a chronic non-specific lesion (n=20, 38.5%) on HPE. Comorbidities (χ2=12.56, P=0.028), endoscopic findings (χ2=10.50, P=0.032), and ulcerations (χ2=20.02, P<0.001) were the significant findings associated with H. pylori infection. Conclusion: The timely identification and expeditious management of H. pylori infection are imperative to mitigate the occurrence of severe complications.